PEMBERDAYAAN KELOMPOK WANITA NELAYAN DALAM PENGEMBANGAN PENGOLAHAN IKAN DI DESA TERUSAN KABUPATEN MEMPAWAH - Maulidi, Maulidi; Adijaya, Mardan (Universitas Esa Unggul, 2019)
The problems experienced by Nurcahaya and Citra Mandiri women fishing groups in the Terusan village in Mempawah Hilir sub-district are the sale of fresh fish, which are relatively cheap. The products are only salted fish and anchovy is made with very simple processing techniques with a relatively low selling price. The solution offered is Processed Fish and Waste Based Diversified Diversification. The purpose of this activity is to improve the standard of living of women fishermen groups through the dissemination of processing technologies for various fish-based processed products that can add to the selling value, be more durable and have higher nutrition. The methods used in this activity are counseling, demonstration, training and guidance in the process of making various processed fish products such as sausages, amplang, nuggets, abon and POC fish waste. Evaluation was carried out on all activities. From this activity it can be concluded that it turned out that more than 50% of the training participants understood the material presented even though there were still 25% who only understood enough. The application of various fish processed products there is 10% of participants will actively continue activities both for family consumption, sold and included in the menu list when there is an event even though most of the participants stated for family consumption (75%).Ã‚Â Keywords: Fish, fishermen, processing.